2013
DOI: 10.1111/iej.12206
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of endodontic working length determination using cone beam computed tomography

Abstract: Using a simplified method, CBCT images of 0.2 mm voxel size can be used to accurately determine endodontic WL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 23 publications
(23 reference statements)
3
42
0
3
Order By: Relevance
“…The few studies that have measured the WL using CBCT have reported different results (Janner et al, 2011;Jeger et al, 2012;Liang et al, 2013;Connert et al, 2014;Lucena et al, 2014). A pilot study comparing CBCT with standard measurements techniques concluded that CBCT could be useful for determining the endodontic WL in combination with clinical measurements (Janner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The few studies that have measured the WL using CBCT have reported different results (Janner et al, 2011;Jeger et al, 2012;Liang et al, 2013;Connert et al, 2014;Lucena et al, 2014). A pilot study comparing CBCT with standard measurements techniques concluded that CBCT could be useful for determining the endodontic WL in combination with clinical measurements (Janner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective controlled clinical study emphasized that CBCT can be used to measure endodontic WL, but that further studies are needed to evaluate whether CBCT can replace initial and WL periapical radiographs (Jeger et al, 2012). Authors showed that CBCT based-root canal length measurements are reliable and can be used to determine an accurate endodontic WL (Liang et al, 2013;Connert et al, 2014). Based on the literature, it can clearly be stated that different results on the WL measurements result from different voxel sizes of the CBCT scans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was useful in patients with cardiac pacemakers where the use of an apex locator is contraindicated and periapical radiography is unreliable. 50,51 Periapical radiography can't detect accurately if there is any existing periapical lesions post endodontic treatment. But, CBCT was useful in detecting the asymptomatic non-healed lesions during the posttreatment followup period to identify the cases requiring retreatment.…”
Section: Assessment Of the Quality Of Root Canal Treatment And Outcommentioning
confidence: 99%